Learning interest of pre-service biology teachers on contextual-based Plant Morphology course - Yulinda, Ratna; Ilma, Silfia (University of Muhammadiyah Malang, 2018)
There was a trend among biology pre-service teachers to have no interest in learning textually, thus the contextual teaching and learning (CTL) implementation is crucial to be done. This study aimed to describe eight indicators of learning interest of biology pre-service teachers on contextual-based Plant Morphology course. As the descriptive research, the instrument used to collect the data in this study was questionnaire. The subjects were biology pre-service teachers in University of Borneo Tarakan, North Kalimantan, Indonesia. The results showed that the student learning activity indicator was categorized as very high (81.72%); while the six indicators which were considered as high criteria were students interest in learning and learning process (71.33%), students attention in learning and learning process (63.67%), study preparation (75,22%), students opinions in the exam activity (61.89%), the impact teacherâs technique and the tactics of learning to the students (85.50%), and student learning outcome (77.17%). The remain indicator (activity of recording material and making of summary in learning) was recognize as medium criteria (57.17%). It can be concluded that contextual-based Plant Morphology course learning must be the main choice in strengthen the understanding of biology pre-service teachers.